Analisis Tindak Tutur Ekspresif dan Direktif pada Video Edukasi Bertema Sains dalam Kanal YouTube Kok Bisa? - Juni Us’ariasih; Talitha Febiola; Anisah Ryan Putri Herlina; Rifqi Nandana Mahardika; Najmi Ali Mumtaz; Asep Purwo Yudi Utomo; Arka Yanitama (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Language is a communication tool used to express an idea or emotion. In linguistics, language is comprehensively explored with the aim of developing understanding and is also used for research. In analyzing the meaning of language, a pragmatic understanding is required. Pragmatics is a linguistic field that examines the interplay between the function and form of speech acts. This research primarily focuses on the analysis of expressive and directive speech acts. Expressive speech acts involve utterances that convey the feelings or thoughts experienced by the speaker. On the other hand, directive speech acts involve utterances intended to encourage or trigger action from the listener. This research aims to obtain, examine, and discuss a variety of speech acts found in educational science-themed videos on the YouTube channel